Hyperferritinemia and Other Factors Related to Glomerular Injury in Beta-Thalassemia Major - Ariningrum, D; Murti, B; Widyastuti, D (KnE Life Sciences, 2019)
Beta-thalassemia major (BTM) is a hereditary hemoglobinopathy, characterized by anemia, increased free radicals and iron overload which can lead to hyperferritinemia, glomerular injury, and kidney dysfunction. This research aimed to analyze the association between hyperferritinemia and urinary podocalyxin (uPCX) as the indicator of glomerular injury in BTM. This retrospective cohort study was conducted on 60 BTM patients aged ≤18 years who came to the pediatrics unit of Dr. Moewardi Hospital Surakarta from April to May 2017. The data were analyzed to determine relative risk and 95%CI for each variable, followed by multivariate analysis with logistic regression. The prevalence of elevated uPCX in BTM patients in this research was 50%. The results showed an association of hyperferritinemia (RR2.51, 95%CI 1.28-4.93, p=0.002), the degree of anemia(RR2.00, 95%CI 1.14-3.52, p=0.01), the number of transfusion (RR 1.75, 95%CI 1.09-2.82, p=0.028), the duration of transfusion (RR 1.83, 95%CI 0.98-3.42, p=0.035), the duration of illness (RR 1.60, 95%CI 0.95-2.72, p=0.071) and the duration of iron chelation therapy (RR 1.58,95%CI 0.79-3.17, p=0.152) with glomerular injury. The multivariate analysis showed that hyperferritinemia and degree of anemia remained significantly associated with glomerular injury (RR 5.46; 95%CI 1.30-23.01; p=0.021 and RR 4.13; 95%CI 1.15-14.85; p=0.030). This study demonstrates a statistically significant association between hyperferritinemia, the degree of anemia, the number of transfusion and the duration of transfusion with kidney injury in BTM patients. Routine monitoring of renal function in BTM is recommended. Keywords: Beta-thalassemia major, hyperferritinemia, urinary podocalyxin, glomerular injury